Development and free distribution of a reagent management system for clinical laboratory operations - YAMASHITA, Fumiaki; WATANABE, Toshiyuki (Japanese Journal of Medical Technology, 2020)
The reagent management system, which is distributed free of charge on the Internet, was developed on the basis of prototypic development and operational experience, aiming at versatility and ease of implementation for the efficient reagent management operations in clinical laboratories. By using the GS1-128 symbol of the barcode written on the reagent package, this system can automatically acquire and record the expiration date and lot information of the reagent necessary for quality control. In addition, according to the setting of the reagent master, the barcode operation can be enabled to record each open date and expiration date by issuing and attaching the control number bar code label to the unit of reagent boxes or the number of individual packages. As a result, the effective inventory management and recording of reagents and the reduction of human error were achieved. This system is distributed free of charge after completion, and the number of downloads and inquiries from the installation facilities strongly supports its necessity and practicability. These results indicate that the development and free distribution of this management system is useful for clinical laboratory operations.